IMPLEMENTATION OF THE GAME BASED LEARNING (GBL) MODEL IN CIVIC EDUCATION TO IMPROVE UNDERSTANDING OF PANCASILA VALUES AT SANGGAR BIMBINGAN KEPONG, MALAYSIA - Muhammad Fajar Syahputra; Ryan Taufika (Journal Analytica Islamica, 2025)
This research was motivated by the low level of understanding of Pancasila values among students at Sanggar Bimbingan Muhammadiyah Kepong, Malaysia. The purpose of this study is to examine the effectiveness of the Game Based Learning (GBL) model in enhancing students' comprehension of Pancasila values within Civic Education. A quantitative method was used, employing a one-group pretest-posttest design. Data were collected through a written test consisting of 20 items and analyzed using a paired sample t-test. The results revealed a significant increase in the average score from 51.15 to 81.15, with a p-value < 0.05. It can be concluded that the GBL model is effective in significantly improving students' understanding of Pancasila values and is particularly relevant for application in non-formal education settings abroad.